"Out here... trash rises": refiguring white trash female identities, historicized bodies and the role of bodily fragmentation in Dorothy Allison`s "Bastard out of Carolina" - Heinisch, Anneliese (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Dorothy Allison`s novel "Bastard out of Carolina" (1992) unflinchingly depicts the fate of a young girl, Ruth Anne Boatwright ("Bone"), who is in danger of succumbing to her oppressive environment marked by social stigmatization, extreme poverty, sexual abuse and neglect. It has been indicated that Bone comes to accept her identity as "a dumb and ugly white trash girl <born to shame and death>" and that her "inherited vulnerability" is practically predetermined because she is her mother`s daughter.
Keywords: white trash; poverty; identity; representations; "Bastard out of Carolina"